2016
DOI: 10.14202/vetworld.2016.337-341
|View full text |Cite
|
Sign up to set email alerts
|

Caprine leptospirosis: Hematobiochemical and urinalyses studies

Abstract: Aim:The present study was designed to evaluate clinicopathological alterations in naturally occurring leptospirosis in goats of South Gujarat region, Gujarat.Materials and Methods:A total 459 blood/serum and 292 urine samples were collected from different districts of South Gujarat region, India. Blood/serum and urine samples were subjected to hematobiochemical analyses and urinalyses. The serum samples were screened for anti-leptospiral antibodies using the microscopic agglutination test (MAT). On the bases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The observed prevalence in the study was concurrent with those of previous studies conducted in India over the years, which have shown variation in the seroprevalence of different livestock species [8,26]. The seroprevalence of 22-29% in Gujarat [18,19,23,27,28]; 9.5-47% in Tamil Nadu [17,[29][30][31]; 27-33% in Kerala [10,32]; 23-29% in Andaman [10,15,33]; and 22-29% in different states located in various agroclimatic zones/region of India [10] in apparently healthy sheep and goats through various surveys has been reported. Further, leptospirosis from the non-endemic regions (Jammu and Kashmir, Uttarakhand, Mizoram, Punjab, Uttar Pradesh, Bihar, Rajasthan, Madhya Pradesh, and Telangana) with seropositivity of 7-15% in sheep and goats have also been reported [10].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The observed prevalence in the study was concurrent with those of previous studies conducted in India over the years, which have shown variation in the seroprevalence of different livestock species [8,26]. The seroprevalence of 22-29% in Gujarat [18,19,23,27,28]; 9.5-47% in Tamil Nadu [17,[29][30][31]; 27-33% in Kerala [10,32]; 23-29% in Andaman [10,15,33]; and 22-29% in different states located in various agroclimatic zones/region of India [10] in apparently healthy sheep and goats through various surveys has been reported. Further, leptospirosis from the non-endemic regions (Jammu and Kashmir, Uttarakhand, Mizoram, Punjab, Uttar Pradesh, Bihar, Rajasthan, Madhya Pradesh, and Telangana) with seropositivity of 7-15% in sheep and goats have also been reported [10].…”
Section: Discussionsupporting
confidence: 88%
“…A high level of seroprevalence among the bovine population, in most of the enzootic Indian states, has been reported, wherein antibodies against more than 20 serogroups with the frequent shift in dominant serovars have been observed over the years in those states, where frequent monitoring is being carried out [12,13,15,16]. It is disappointing those studies on the prevalence and distribution of serovars in sheep and goats are very scanty in the world, including India, except for a few isolated studies [15,[17][18][19]. Leptospirosis in sheep and goats may present as an acute or as a subclinical infection and the affected animals may show pyrexia, conjunctivitis, jaundice, anemia, anuria, hemoglobinuria, loss of appetite, irritability, diarrhea, mastitis, haemogalactia, opaque furs, epidemic abortions, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detecting the presence of leptospires in urine or in blood or tissues is difficult [88]. Many authors have detected leptospires in various body fluids of cattle, sheep, and goat using dark-field microscopy and confirmed by PCR, without bacterial isolation [62].…”
Section: Histopathologymentioning
confidence: 99%
“…The occurrence of antibodies against many serovars without leptospiral isolation cannot establish a diagnosis of the disease [88], even during the early acute phase of the disease, where IgM ELISA can give a presumptive diagnosis of leptospirosis [89]. Unlike ELISA, PCR can accurately confirm the disease.…”
Section: Histopathologymentioning
confidence: 99%